MATHEMATICAL MODEL FOR DEPOSITION BY SPRAY PROCESS - Santos De la Cruz, Eulogio (1998)
For all the phenomenon is known faith and corrosion effects which arise which are evident in the deterioration of materials, equipment, etc.. This phenomenon is present in all branches of industry, transport and construction.